Trajectory generation from motion capture for a planar biped robot in swing phase (2015)
This paper proposes human motion capture to generate movements for the right leg in swing phase of a biped robot restricted to the sagittal plane -- Such movements are defined by time functions representing the desired angular positions for the joints involved -- Motion capture performed with a Microsoft Kinect TM camera and from the data obtained joint trajectories were generated to control the robot’s right leg in swing phase -- The proposed control law is a hybrid strategy; the first strategy is based on a computed torque control to track reference trajectories, and the second strategy is based on time scaling control ensuring the robot’s balance -- This work is a preliminary study to generate humanoid robot trajectories from motion capture